3D FEM simulation of the turning process of stainless steel 17-4PH with differently texturized cutting tools. (May 2019) - Liu, Guoliang; Huang, Chuanzhen; Su, Rui; Özel, Tuğrul; Liu, Yue; Xu, Longhua
Highlights: An orthogonal cutting-based method was modified to obtain J–C model parameters. J–C material model of stainless steel 17-4PH was newly obtained and verified. Curvilinear micro-grooved tools were newly designed and tested by 3D FEM. New designed tools can reduce friction, cutting forces and temperature notably. New designed tools can weaken stress concentration on cutting edges. Abstract: Micro-texturing techniques are applied to improve the performance of cutting tools by improving the tribological performance. However, sharp edges of linear micro-grooved tool designs may adversely affect tool-chip contact, create interlocking effects, and weaken the potential benefits. This paper investigates new designs in curvilinear micro-grooves on the cutting tool rake face to reduce the interlocking effect and further improve the performance. A modified methodology that uses an orthogonal cutting model and inverse analysis was utilized to determine the Johnson–Cook (J–C) constitutive material model parameters for stainless steel 17-4PH. The finite element method (FEM) simulation results in force predictions confirmed that this methodology is suitable to obtain J–C model parameters used in high-speed machining regimes. Then, three-dimensional (3D) simulations for rough and finish turning were developed and validated for machining with the non-textured cutting tool. The performance of cutting with curvilinear micro-grooved tools was investigated by 3D FEM simulations. These newly designed micro-grooved tools showed improved performance in tool-chip friction, chip formation, cutting force, temperature, and tool stress fields than non-textured and linear micro-grooved designs. Graphic abstract: Image, graphical abstract